Analysis of the Efficiency of Composite Supports in Electric Networks of the Republic of Belarus - M. I. Fursanov; P. A. Sazonov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Modern conditions for the development of the electric power industry increase the requirements in the field of technical conditions and reliability; thus, in a number of Western countries electric networks are being restructured on the basis of safe, environmentally friendly and reliable composite supports. The article analyzes the structure, design and methods of construction of overhead power lines with composite supports that are more promising than traditional ones. The properties, main characteristics and advantages of materials for the production supports of fiberglass and of wood are considered. The advantages and disadvantages of composite and wooden racks are compared and it is shown that most of the requirements for the supports of overhead power lines are met by composite supports. It is discovered that the existing and promising solutions that enable effective use of composite supports in the construction of an overhead line are quite diverse. Currently, in the electrical networks of Western countries, the most common structural model of the construction of an overhead line is the one the one that alternates composite and wooden supports in a certain sequence. The best option of the use of composite supports along with wood ones is the following ratio: four composite supports to one wooden one (method of construction “4/1”). The advantages of this method of construction of the power line are presented, viz. a significant increase in the mechanical strength of the structure of supports and wires as well as the safety of their maintenance. The results of technical and economic calculation that confirm the advantage of constructing a 10 kV distribution line according to the “4/1” scheme are presented. The implementation of composite supports in the electric networks of the Republic of Belarus in the long term will allow obtaining a tangible financial effect by reducing the cost of operation of the overhead line and because of a significant period of operation of composite racks, which is an undoubted advantage in conditions of the modern market economy.